2017
DOI: 10.1039/c7ra07578b
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a new renewable sesame protein adhesive modified by urea in the absence and presence of zinc oxide

Abstract: Sesame protein (SP) is a new renewable resource for wood adhesives because of its brilliant performance, which is non-toxic and harmless to human health during the process of using plywood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…The viscosity of the USP/GUSP adhesives gradually decreased with increasing shear rate. This phenomenon showed that the sesame protein adhesives were shear-thinning fluids, and this result was consistent with Wei et al (2017). The initial viscosity of the USP adhesive without glyoxal addition was 71560 mPa•s.…”
Section: Rheology Properties Analysissupporting
confidence: 81%
See 1 more Smart Citation
“…The viscosity of the USP/GUSP adhesives gradually decreased with increasing shear rate. This phenomenon showed that the sesame protein adhesives were shear-thinning fluids, and this result was consistent with Wei et al (2017). The initial viscosity of the USP adhesive without glyoxal addition was 71560 mPa•s.…”
Section: Rheology Properties Analysissupporting
confidence: 81%
“…Sesame (Sesamum indicum L.) is primarily cultivated in Asian and African countries as a traditional oilseed crop, while China has been the first and greatest sesame production and consumption industry in the world (Pathak et al 2014;Wei et al 2017). Sesame seeds have the highest protein (25%) and oil content (55%) among all oilseed crops (Raja et al 2007a,b;Wei et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [9] found that undecylenic acid with hydrophobic carbon chain and active carboxyl group was an efficient modifier to enhance the wet shear strength of soya protein isolate-based adhesives. Wei et al [10] discovered that after adding zinc oxide, the wet shear strengths of the sesame protein-based adhesives were improved due to the chelation reaction between sesame protein and Zn 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al . [ 10 ] discovered that after adding zinc oxide, the wet shear strengths of the sesame protein-based adhesives were improved due to the chelation reaction between sesame protein and Zn 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Plant proteins are high-quality renewable resources for formaldehyde-free wood adhesives, and have received widespread attention. A number of previous studies have focused on plant protein-based adhesives, including adhesives based on soy [6], cotton [7], wheat [8] and sesame proteins [9]. Nevertheless, there are few studies on the preparation of wood adhesives based on peanut proteins.…”
Section: Introductionmentioning
confidence: 99%